New theories of relativistic hydrodynamics in the LHC era - Florkowski, Wojciech; Heller, Michal P; Spali ski, Micha (Reports on progress in physics, 2018)
The success of relativistic hydrodynamics as an essential part of the phenomenological description of heavy-ion collisions at RHIC and the LHC has motivated a significant body of theoretical work concerning its fundamental aspects. Our review presents these developments from the perspective of the underlying microscopic physics, using the language of quantum field theory, relativistic kinetic theory, and holography. We discuss the gradient expansion, the phenomenon of hydrodynamization, as well as several models of hydrodynamic evolution equations, highlighting the interplay between collective long-lived and transient modes in relativistic matter. Our aim to provide a unified presentation of this vast subject-which is naturally expressed in diverse mathematical languages-has also led us to include several new results on the large-order behaviour of the hydrodynamic gradient expansion.